MEMBANGUN KOMITMEN ORGANISASI BERBASIS PADA ISLAMIC LEADERSHIP DAN KNOWLEDGE DONATING BAGI KARYAWAN KOPERASI SYARI’AH BMT KABUPATEN SEMARANG - Natoil Natoil (JURNAL STIE SEMARANG, 2018)
The purpose of this research is to test the influences of Islamic leadership, and knowledge donating, on organizational commitment moderated by spiritual motivation. Using these variables, the usage of these variables are able to solve the arising problem within employees sharia cooperatives BMT Kabupaten Semarang. Statement of this problem is how increase organizational commitment. The samples size of this research is 80 employees sharia coopertives BMT Kabupaten Semarang. The results show that Islamic leadership, and knowledge donating, on organizational commitment moderated by spiritual motivation. The effect of Islamic leadership on organizational commitment are significant; The effect of knowledge donating on organizational commitment are significant; spiritual motivation moderating influence knowledge donating on organizational commitment are significant.